The Consumption of Beeswax Alcohol (BWA, Raydel®) Improved Zebrafish Motion and Swimming Endurance by Protecting the Brain and Liver from Oxidative Stress Induced by 24 Weeks of Supplementation with High-Cholesterol and D-Galactose Diets: A Comparative Analysis Between BWA and Coenzyme Q10 - Kyung-Hyun Cho; Yunki Lee; Ashutosh Bahuguna; Sang Hyuk Lee; Chae-Eun Yang; Ji-Eun Kim; Hyo-Shin Kwon (Antioxidants)
The prolonged consumption of D-galactose (Gal) has been associated with severe damage in the liver and brain via exacerbation of oxidative stress, non-enzymatic glycation, and the aging process. The current study was initiated for a comparative assessment of beeswax alcohol (BWA, final 0.5% and 1.0% w/w) and coenzyme Q10 (CoQ10, final 0.5% and 1.0% w/w) against high-cholesterol (HC, final 4%, w/w) and -galactose (Gal, final 30%, w/w)-induced adverse events in zebrafish during 24 weeks of consumption. The survivability of zebrafish decreased to 82.1% due to HC+Gal exposure, but this was substantially improved (91.0%) with the consumption of 0.5% and 1.0% BWA. In contrast, no protective effect of CoQ10 consumption (1.0%) was observed on the survivability of zebrafish. Nevertheless, both BWA and CoQ10 displayed a significant (p < 0.001) preventive effect against HC+Gal-induced body weight enhancement. The HC+Gal-induced cognitive changes, marked by staggered and confused swimming behavior, and retarded swimming speed and motion patterns (restricted to the bottom of the tank), were efficiently restored by BWA. A significantly higher residence time in the upper half of the tank, 3.1-and 4.5-fold reduced latency time along with 3.5-fold and 4.1-fold higher swimming distance, was logged in the 0.5% and 1.0% BWA groups, respectively, than the zebrafish that consumed HC+Gal. In addition, BWA effectively enhanced plasma ferric ion reduction (FRA) and paraoxonase (PON) activity and alleviated the total cholesterol (TC), triglyceride (TG), and blood glucose levels disrupted by the consumption of HC+Gal. Also, the HC+Gal-alleviated plasma high-density lipoprotein-cholesterol (HDL-C) was 2.6-fold (p < 0.001) enhanced in the group that consumed 1.0% BWA, which was significantly 1.5-fold (p < 0.001) better than the effect of 1.0% CoQ10. Similarly, BWA displayed a superior impact over CoQ10 to mitigate HC+Gal-induced plasma AST and ALT levels, hepatic IL-6 production, generation of oxidized species, cellular senescence, and fatty liver changes. Moreover, BWA protects the brain against HC+Gal-induced oxidative stress, apoptosis, and myelin sheath degeneration. Conclusively, compared to CoQ10, BWA efficiently can the HC+Gal-impaired brain and liver functionality to subside and improves the dyslipidemia and cognitive behavior of zebrafish.